2018
DOI: 10.1002/cne.24413
|View full text |Cite
|
Sign up to set email alerts
|

The Second Visual System of The Tree Shrew

Abstract: This review provides a historical account of the discovery of secondary visual pathways (from retina to the superior colliculus to the dorsal thalamus and extrastriate cortex), and Vivien Casagrande's pioneering studies of this system using the tree shrew as a model. Subsequent studies of visual pathways in the tree shrew are also reviewed, beginning with a description of the organization and central projections of the tree shrew retina. The organization and connectivity of second visual system components that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 123 publications
(191 reference statements)
0
31
0
Order By: Relevance
“…In contrast, V1 lesions in tree shrews, which are closely related to primates as members of the Euarchontoglire superorder, leave many visual abilities intact (see [85] for review). After bilateral ablations of primary visual cortex, tree shrews are capable of form and pattern vision, localizing visual objects in space, following a moving food item, grasping food, and avoiding objects while running on the floor [86][87][88][89].…”
Section: Lesions Of Primary Visual Cortex (V1) In Rodents and Tree Shmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, V1 lesions in tree shrews, which are closely related to primates as members of the Euarchontoglire superorder, leave many visual abilities intact (see [85] for review). After bilateral ablations of primary visual cortex, tree shrews are capable of form and pattern vision, localizing visual objects in space, following a moving food item, grasping food, and avoiding objects while running on the floor [86][87][88][89].…”
Section: Lesions Of Primary Visual Cortex (V1) In Rodents and Tree Shmentioning
confidence: 99%
“…Deeper lesions of the superior colliculus that included projections to motor centers in the brainstem, produced tree shrews that were unable to track objects or freely move about, and the tree shrews appeared to be blind [90,91]. From such evidence, Petry and Bickford [85] concluded that lesions of the superior colliculus impair vision more in tree shrews than lesions of V1.…”
Section: Lesions Of Primary Visual Cortex (V1) In Rodents and Tree Shmentioning
confidence: 99%
“…The tree shrew ( Tupaia belangeri ) is a small mammal similar in appearance to squirrel, widely distributed in South Asia, Southeast Asia and Southwest China [1]. Due to several specific characteristics, such as small adult body size, short reproductive and life cycle, low cost of maintenance, high brain-to-body mass ratio, and close affinity to primates, the tree shrew has been proposed as an alternative laboratory animal (nonhuman primate) in biomedical researches in recent years [2–4]. Currently, several studies have used this animal for human disease investigations, including hepatitis C virus [5], and Epstein-Barr virus [6], as well as brain development and aging [7, 8], social stress and depression [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…Other nongenomic evidences of morphological and anatomical characteristics in the tree shrew brain also support the relationship of tree shrews to primates (McCollum & Roberts, ; Ni et al, ; Ni et al, ; Rice, Roberts, Melendez‐Ferro, & Perez‐Costas, ; Romer et al, ). Previous studies have indicated that the tree shrews is widely used to study the visual system (Baldwin, Balaram, & Kaas, ; Petry & Bickford, ), motor system (Baldwin, Cooke, & Krubitzer, ), social stress (Fuchs & Flugge, ; Wang et al, ) and other neural systems. The Tree Shrew ( Tupaia glis ) atlas by Tigges and Shantha () is comprehensive and includes photographs of Nissl‐stained sections and plates showing fiber tracts (cut at 50‐Όm intervals) along with stereotaxic coordinates based on their alignment of the skull and brain for blocking.…”
Section: Introductionmentioning
confidence: 99%